Hallway conversations: A narrative research on pedagogical coordination and continued training of teachers who teach Mathematics in the Early Years - de Santana, Marcela Lopes [UNESP]; Gonçalves, Harryson Júnio Lessa [UNESP] (FapUNIFESP (SciELO), 2020)
This paper presents the dissertation entitled Hallway conversations: pedagogical coordination, narratives, experiences, continuous formation in service in the context of the mathematics of the initial years of the elementary school a narrative research that aimed at investigating how the pedagogical coordinators, when revisiting their action through the narratives, report their dealings with the challenges present in their role as teacher/educators and how they carry out this continuing education focused on Mathematics taught by the teachers in the Early Years of Elementary School; and discussing the continuing education focused on the Mathematics, as well as the curriculum explained by the narratives of the pedagogical coordinators’ tasks for the Early Years of Elementary School. It explores the language and subversion of academic writing norms, combining form and content to produce meaning. Some passages are written in chronicles. The considerations metaphorically express the synthesis of the challenges of pedagogical coordination and discuss education through the experience/sense pair, as suggested by Jorge Larrosa, the theoretical reference of this work. The methodology consists of going from conversations, from the coordinators’ narratives, to a thought-oriented conversation, through research on other contexts of coordination, expressed here in footnotes. And then, making a resignified return for the pedagogical and curricular experiences, through the chronicles. It is concluded that it is necessary to think about training each and every person to use mathematical knowledge. This requires boldness and utopia, it requires the coordinator to avoid traps, subversion, and creativity, in order to escape the technical curriculum in favor of human dignity.
Conversas de Corredores: Uma pesquisa narrativa sobre coordenação pedagógica e formação continuada de professores que ensinam Matemática nos Anos Iniciais
Keywords: Curriculum; Mathematical Education; Narratives; Pedagogical Coordinator